An oxide-type catalyst for catalytic pyrolysis to prepare aliphatic isocyanate
By using the ZIF-8 imidazole amuctone skeleton to prepare the MOZ/ZNO oxide nano-catalyst, the problem of low catalyst catalyst catalytic activity and uneven element distribution of the existing catalysts have been solved, and the high-efficiency catalytic thermal alistanic amino amino amino aliploma isolate is aliphed. , Significantly improved the response efficiency and yield.
Patent Information
- Application Number
- CN202310332086.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-31
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-31
AI Technical Summary
When preparing aliphatic isocyanates, the existing oxide catalysts have problems such as low catalytic activity, small specific surface area, low oxygen vacancies and uneven element distribution, resulting in low reaction efficiency and yield.
By using the ZIF-8 imidazole boilestone skeleton as the front-drive body, the impregnation method is used to replace some ZN2+ions to obtain the MOZ/ZNO oxide nano-catalyst. This catalyst is formed under high temperature roasting at 400 to 600 ° C, which has a high ratio area, rich oxygen and empty position and uniform element distribution.
The high -efficiency catalytic thermal alistanic amino amino amino amino ammonia isolates the alipanocyanate. The ADU conversion rate can reach up to 96.5 %, the ADI revenue can reach up to 88 %, which significantly improves the response efficiency and yield. performance.
Smart Images

Figure CN116459822B_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of fine chemical product synthesis, and relates to an oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis, and application of the catalyst in preparing aliphatic isocyanate by catalytic pyrolysis of aliphatic carbamate. Background Art
[0002] Aliphatic isocyanate (ADI) is one of the important high-grade raw materials for synthesizing polyurethane. Compared with aromatic diisocyanates (TDI, MDI), ADI has a linear saturated chemical structure. The polyurethane coatings made with it as raw material have oil resistance and wear resistance, as well as good light stability and yellowing resistance. At present, the traditional synthesis process of ADI mainly adopts the phosgene method. Due to the shortcomings of phosgene being highly toxic and the corrosion of equipment by the by-product HCl in the production process, the use of phosgene is strictly controlled, and the application of the phosgene method is limited. Therefore, the development of non-phosgene methods has always been a hot spot in global technology development.
[0003] The non-phosgene method mainly includes carbon dioxide carbonylation, nitro compound carbonylation, chlorosilane method, isocyanate displacement, Curtius rearrangement, Lossn rearrangement, halogenated isocyanate synthesis, and carbamate thermal decomposition. However, most of the non-phosgene methods have disadvantages such as difficult to control the reaction path, difficult to separate a large number of by-products, and expensive raw material costs. Among them, the carbamate thermal decomposition method has become the most industrially promising process route for the non-phosgene synthesis of isocyanates due to its mild reaction conditions and recyclable by-products. This route can be divided into a gas phase method and a liquid phase method. The liquid phase method is used to pyrolyze aliphatic carbamates to prepare aliphatic isocyanates. By adding an inert solvent to dilute the reactants, the group concentration is reduced, thereby inhibiting the occurrence of side reactions and promoting the thermal cracking. In addition, the inert solvent can also be used as a heat medium to provide energy for the reaction system to keep the reaction temperature consistent. Compared with the gas phase method, the reaction temperature of the liquid phase method is lower than that of the gas phase method, and the provision and control of reaction heat are easier than that of the gas phase method. Therefore, the liquid phase method is more promising in the commercial production of isocyanates.
[0004] Aliphatic isocyanates can be prepared by pyrolysis of aliphatic carbamates in the liquid phase with or without a catalyst. However, in the absence of a catalyst, the thermal cracking rate of carbamates is relatively low, and the conversion rate and yield are low. Therefore, efficient catalysts play an important role and will be the key to the realization of non-phosgene synthesis of isocyanates.
[0005] The researchers used zinc powder as a catalyst, nitrobenzene and dioctyl sebacate (DOS) as a mixed solvent to synthesize MDI, reacted at 280°C for 1.5h, and the MDI yield was 84.3%. However, the use of metal elements as catalysts has the problem of easy deactivation and difficulty in recycling. CN101195590A uses ionic liquid as a hot solvent and a supported metal oxide as a catalyst to pyrolyze HDU to prepare HDI, wherein the carrier of the catalyst is selected from silicon oxide or aluminum oxide, and the active component is selected from one or two of copper oxide, nickel oxide, zinc oxide, and zirconium oxide. The final yield of HDI can reach 74-80%, but the design of efficient catalysts is not involved, and the high price of ionic liquids hinders its industrial promotion. CN102964272A uses a supported solid catalyst, the carrier is selected from silicon dioxide, zirconium oxide, diatomaceous earth or molecular sieve, and the active component of the catalyst is selected from zinc oxide, aluminum oxide, nickel oxide, cobalt tetraoxide, chromium trioxide and other oxides. However, the above catalysts have the disadvantages of few active centers, small specific surface area, and low oxygen vacancy concentration, which are not conducive to reaction mass transfer and heat transfer. There is also a case where ZnO-Al2O3 is used as a catalyst and dioctyl phthalate is used as a heat carrier. Under the optimal process conditions of vacuum degree of 9.0kPa and temperature of 240°C, the HDI yield is 81.1%, but the catalyst is only a mixture of commercial grade ZnO-Al2O3, which has the disadvantage of uneven element distribution. Some researchers have also derived CuO / ZnO catalysts by coprecipitation method, which show better activity compared with single-component physical mixed oxides. Using polyethylene glycol dimethyl ether as solvent, the reaction is 175°C for 1h, and the HDI yield is as high as 75%. However, the catalyst has the disadvantages of low polarity and small specific surface area, resulting in a low HDI yield. Researchers have found that nanostructured metal oxides are also effective catalysts for thermal cracking reactions. Nano Cu2O catalysts prepared by hydrolysis have higher active centers. The MDI selectivity is 86% after reacting for 12 minutes at 220°C and 0.6kPa. Compared with common commercial-grade oxides, the thermal decomposition reaction was intensified and the yield of isocyanate was improved. The proposed nanocatalyst showed more effective performance in the synthesis of isocyanates.
[0006] In summary, oxide-type catalysts are a good choice for the preparation of isocyanates by pyrolysis of carbamates, with the advantages of relatively stable structure and easy recycling. However, the composite oxide-type catalysts prepared by existing mixing methods, precipitation methods, etc. do not have a nanostructure, and have the characteristics of small specific surface area, low oxygen vacancy concentration, and uneven element distribution, resulting in low catalytic activity. Rich oxygen vacancy concentration, metal elements with high polarity ratio, and nanomaterials with high specific surface area can promote the cleavage of carbamates to remove methanol molecules, and have a significant promoting effect on the pyrolysis reaction. Summary of the invention
[0007] The present invention aims to provide an oxide-type catalyst (MO z / ZnO) to achieve efficient pyrolysis of aliphatic methyl carbamate (ADU) to prepare aliphatic isocyanate (ADI).
[0008] The purpose of the present invention can be achieved through the following technical solutions:
[0009] An oxide catalyst for preparing aliphatic isocyanate by catalytic pyrolysis, wherein Zn(NO3)2·6H2O and 2-methylimidazole are used as raw materials to prepare ZIF-8 imidazole zeolite framework; and metal nitrate (M(NO3) x ·yH2O) makes the metal ion M x+ Replacement of part of Zn in the imidazolate framework of ZIF-8 2+ , and obtain the M-ZIF-8 precursor; the M-ZIF-8 precursor is calcined at 400-600°C for 1-10h in an air atmosphere to obtain MO z / ZnO oxide type nanocatalyst.
[0010] The reaction solvent used to prepare the ZIF-8 imidazole zeolite framework is methanol, deionized water or N,N-dimethylformamide (DMF); the reaction solvent used in the impregnation method is methanol, deionized water or N,N-dimethylformamide. Preferably, the reaction solvent used in the impregnation method is the same as the reaction solvent used to prepare the ZIF-8 imidazole zeolite framework.
[0011] Another object of the present invention is to provide a method for preparing the oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis, comprising: dissolving Zn(NO3)2·6H2O in a reaction solvent to form a zinc nitrate solution; dissolving 2-methylimidazole in a reaction solvent to form a 2-methylimidazole solution; mixing the zinc nitrate solution and the 2-methylimidazole solution evenly, aging at room temperature for 6 to 12 hours, and obtaining a suspension containing a ZIF-8 imidazole zeolite framework; and adding a metal nitrate (M(NO3) x ·yH2O), stirred to dissolve, aged at room temperature for 1 to 6 hours, the mixed solution was centrifuged to obtain a precipitate, the precipitate was washed with fresh methanol, the solid was collected, and the solid was dried to obtain an M-ZIF-8 precursor; the M-ZIF-8 precursor was calcined at a high temperature of 400 to 600°C in an air atmosphere for 1 to 10 hours to obtain MO z / ZnO oxide type nanocatalyst.
[0012] The zinc nitrate solution is prepared by mixing a reaction solvent with Zn(NO3)2·6H2O in a mass ratio of 16:1 to 27:1. The 2-methylimidazole solution is prepared by mixing a reaction solvent with 2-methylimidazole in a mass ratio of 8:1 to 14:1.
[0013] The molar ratio of the 2-methylimidazole to Zn(NO3)2·6H2O is 5:1 to 7.5:1.
[0014] The molar ratio of the metal nitrate to Zn(NO3)2·6H2O is 0.1:1 to 0.4:1, preferably 0.1:1 to 0.2:1.
[0015] The metal nitrate (M(NO3) x ·yH2O) is selected from one of Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O, Al(NO3)3·9H2O, and Cr(NO3)3·9H2O.
[0016] Correspondingly, the M-ZIF-8 precursor is one of Zn-ZIF-8, Cu-ZIF-8, Co-ZIF-8, Al-ZIF-8, and Cr-ZIF-8.
[0017] Said MO z / ZnO oxide is one of ZnO / ZnO, CuO / ZnO, Co3O4 / ZnO, Al2O3 / ZnO, and Cr3O4 / ZnO.
[0018] The solid is first dried at a temperature of 60-70°C for 1-2 hours, and then heated to 80-100°C and dried for 6-10 hours, or the solid is dried at 80-100°C for 6-10 hours.
[0019] Preferably, the calcination temperature is 450-550°C.
[0020] As the preferred technical scheme of the method for preparing the oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis of the present invention, when the metal nitrate (M(NO3) x ·yH2O) is selected from Zn(NO3)2·6H2O, the following method can also be used: dissolving Zn(NO3)2·6H2O in a reaction solvent to form a zinc nitrate solution; dissolving 2-methylimidazole in a reaction solvent to form a 2-methylimidazole solution; mixing the zinc nitrate solution and the 2-methylimidazole solution evenly, aging at room temperature for 6 to 12 hours to obtain a ZIF-8 imidazole zeolite framework, centrifuging the mixed solution to obtain a precipitate, washing the precipitate with fresh methanol, collecting the solid, drying the solid, and then calcining at a high temperature of 400 to 600°C in an air atmosphere for 1 to 10 hours to obtain an oxide-type nanocatalyst.
[0021] Another object of the present invention is to provide the use of the oxide-type nanocatalyst in catalytic pyrolysis of aliphatic carbamate (ADU) to prepare aliphatic isocyanate (ADI).
[0022] A method for preparing aliphatic isocyanate by catalytic pyrolysis of aliphatic carbamate, comprising: using the oxide-type nanocatalyst as a catalyst and a high boiling point solvent as a reaction solvent, catalytically pyrolyzing the aliphatic carbamate to prepare aliphatic isocyanate; wherein the reaction temperature is 220-260°C, the reaction pressure is 0.01-0.1MPa, and the reaction time is 20-60min.
[0023] Preferably, the reaction temperature is 230-250° C., the reaction pressure is 0.01-0.09 MPa, and the reaction time is 30-50 min.
[0024] The aliphatic carbamate is selected from one of pentamethylene dicarbamate (PDU), hexamethylene dicarbamate (HDU), and isophorone dicarbamate (IPDU).
[0025] The high boiling point solvent is an organic solvent with a boiling point of 330-450° C.; specifically, it is selected from one of dibutyl phthalate, dioctyl phthalate, dibutyl sebacate, and dioctyl sebacate, preferably one of dibutyl sebacate and dioctyl sebacate.
[0026] The mass ratio of the aliphatic carbamate to the high boiling point solvent is 0.025:1 to 0.075:1, preferably 0.0375:1 to 0.05:1.
[0027] The mass ratio of the catalyst to the aliphatic carbamate is 0.025-0.125:1, preferably 0.05:1-0.1:1.
[0028] The beneficial effects of the present invention are embodied in:
[0029] The present invention uses ZIF-8 imidazole zeolite framework as a precursor to prepare MO with high polarity ratio, large specific surface area, high oxygen vacancy concentration and uniform element distribution. z / ZnO composite oxide catalyst. This catalyst inherits the nano-morphology and porous structure of the ZIF-8 imidazole zeolite framework, with a pore size of 2 to 50 nm. Its high surface area and uniform element distribution are conducive to the exposure of abundant surface active sites, which is beneficial to mass transfer and heat transfer, and increases the utilization rate of active sites. The abundant oxygen vacancies are more likely to form hydrogen bonds with the H on the NH bond on the carbamate molecule, and the high polarity ratio of M + -Zn 2+ The ion has a stronger electron-withdrawing property and is more likely to combine with the O on the CO bond of the carbamate molecule, and finally remove a molecule of methanol from the methyl carbamate bond in the carbamate molecule, thereby generating the isocyanate in the target product molecule.
[0030] Compared with the common oxide-type catalyst preparation method, the preparation method of the present invention has a simple process, mild conditions, and is green and environmentally friendly. The prepared catalyst is used to catalyze the pyrolysis of carbamate to prepare aliphatic isocyanate, which strengthens mass transfer and heat transfer, has high catalytic activity and selectivity, and the ADU conversion rate can reach up to 96.5%, and the ADI yield can reach up to 88%, which has a significant promoting effect on the catalytic pyrolysis of ADU to prepare ADI. In addition, the composite oxide-type nanocatalyst of the present invention has good reusability, and finally realizes the efficient preparation of aliphatic isocyanate products. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 XRD diagram of ZnO / ZnO-0.1-X prepared at different calcination temperatures in Example 1.
[0032] Figure 2 The SEM spectra of ZnO / ZnO-0.1-X prepared at different calcination temperatures in Example 1.
[0033] Figure 3 This is the effect of the dosage of ZnO / ZnO-0.1-500 on the catalytic effect in Example 1.
[0034] Figure 4 These are the XRD diagrams of the catalyst ZnO / ZnO-0.1-500 of Example 1, the catalyst CuO / ZnO-0.1 of Example 2, the catalyst CuO / ZnO-0.2 of Example 3, and the catalyst CuO / ZnO-0.4 of Example 7.
[0035] Figure 5 This is the Mapping-EDX element distribution map of the catalyst CuO / ZnO-0.1 prepared in Example 2.
[0036] Figure 6 This is the XPS graph of the catalyst CuO / ZnO-0.2 prepared in Example 3.
[0037] Figure 7 These are SEM images of the catalyst ZnO / ZnO-0.1-500 of Example 1 and the catalyst CuO / ZnO-0.2 of Example 3.
[0038] Figure 8 This is the TEM image of the catalyst CuO / ZnO-0.2 prepared in Example 3.
[0039] Fig. 9 The BET diagram of the catalyst CuO / ZnO-0.2 prepared in Example 3 and the commercial grade ZnO in Comparative Example 1. DETAILED DESCRIPTION
[0040] In order to make the technical scheme of the present invention clearer, the present invention is described in detail below in conjunction with specific examples. These examples are only used to describe the embodiments of the present invention and should not be construed as limiting the scope of the present invention. In the examples, the reagents used are not indicated by the manufacturer, and all can be conventional products obtained by commercial purchase.
[0041] Example 1
[0042] Dissolve 3.0g Zn(NO3)2·6H2O in 100mL methanol to form solution A; dissolve 6.0g 2-methylimidazole in 100mL methanol to form solution B; add solution A to solution B, stir thoroughly, mix evenly, and age at room temperature for 6h; then add 0.3g Zn(NO3)2·6H2O, stir to dissolve, and age at room temperature for 1h; centrifuge the mixture to obtain a precipitate, wash the precipitate with fresh methanol, and collect the solid; dry the solid at 60°C for 2h, then heat to 80°C and dry for 6h to obtain a Zn-ZIF-8-0.1 precursor.
[0043] In air atmosphere, the Zn-ZIF-8-0.1 precursor was calcined at different temperatures (300, 400, 500, 600 °C) for 1 h to obtain oxide-type nanomaterials, denoted as ZnO / ZnO-0.1-X (X is temperature).
[0044] Depend on Figure 1 It can be seen that the structure of the Zn-ZIF-8-0.1 precursor was not broken after calcination at 300°C. The diffraction peaks of ZnO / ZnO-0.1-400 are consistent with the diffraction peaks of the standard card ZnO (JCPDS NO.36-1451), indicating that the ZnO derive path from the Zn-ZIF-8-0.1 precursor is feasible. However, ZnO / ZnO-0.1-400 has an amorphous bulge peak near 20° because some organic ligands and carbon deposits still exist after 400°C. With the increase of calcination temperature, it can be found that the diffraction peaks of ZnO / ZnO-0.1-500 and ZnO / ZnO-0.1-600 correspond to the standard ZnO card, indicating that ZnO materials with better crystallinity are obtained.
[0045] Figure 2SEM spectra of ZnO / ZnO-0.1-X obtained from Zn-ZIF-8-0.1 precursor at different calcination temperatures. (a) is Zn-ZIF-8-0.1 precursor, showing uniform and regular rhombic dodecahedron morphology; (b) is ZnO / ZnO-0.1-300, and it is found that the morphological structure of the material is not destroyed, and the original morphology of Zn-ZIF-8-0.1 precursor is still maintained, which is consistent with the XRD analysis results; (c) is ZnO / ZnO-0.1-400, and it can be observed that the morphology of Zn-ZIF-8-0.1 precursor begins to change, the skeleton part loses organic ligands, and a carbon layer is formed on the surface, which is also consistent with the XRD analysis results; (d) is ZnO / ZnO-0.1-500. At this time, the Zn-ZIF-8-0.1 precursor is completely converted to obtain nanoporous ZnO, which is composed of small nanoparticles, making it highly porous and retaining the good polyhedral morphology of the Zn-ZIF-8-0.1 precursor; (e) is ZnO / ZnO-0.1-600. Agglomeration is obviously observed. The particle size of ZnO becomes larger, which will lead to a decrease in specific surface area and affect the catalytic activity; (f) is the SEM image of commercial-grade ZnO, showing an irregular large-particle non-porous structure.
[0046] Characterization methods such as XRD, BET, XPS, and SEM-Mapping show that the catalyst ZnO / ZnO-0.1-500 has uniform element distribution, inherits the nano-morphology and porous structure of the organic metal framework precursor, and has a higher polarity ratio I 002 / 100 (ZnO) = 84.8%, specific surface area 32.28m 2 / g, oxygen vacancy concentration O ads / O lat It is 80.17%.
[0047] 4g HDU, 80g dibutyl sebacate (DBS), 0.3g ZnO / ZnO-0.1-X or Zn-ZIF-8-0.1 precursor were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced to replace the air in the device, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40min. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. The results are shown in Table 1.
[0048] Table 1. Results of investigation on catalytic performance of ZnO / ZnO-0.1-X
[0049] Material HDU conversion rate HDI yield Zn-ZIF-8-0.1 55.3% 28.1% ZnO / ZnO-0.1-300 58.6% 34.2% ZnO / ZnO-0.1-400 89.5% 73.2% ZnO / ZnO-0.1-500 94.3% 81.5% ZnO / ZnO-0.1-600 92.1% 77.6%
[0050] As can be seen from Table 1, the Zn-ZIF-8-0.1 precursor has almost no catalytic activity for the pyrolysis reaction of HDU, indicating that the ZN structure in the ZIF-8 framework cannot become the active site for the pyrolysis reaction of HDU. ZnO / ZnO-0.1-300 also shows low catalytic activity because the Zn-ZIF-8-0.1 precursor is not heated at 300°C to destroy the original ZN structure and convert it into ZnO. The ZnO material derived from the Zn-ZIF-8-0.1 precursor at 400°C gradually transforms into a ZO structure, thereby increasing the catalytic pyrolysis performance. Under the catalysis of ZnO / ZnO-0.1-400, the HDI yield can reach 73.2%, and ZnO / ZnO-0.1-500 shows the best catalytic performance, with an HDI yield of 81.5%, which is significantly better than the catalytic performance of commercial-grade ZnO (Comparative Example 1). As the calcination temperature increases, the catalytic performance of ZnO / ZnO-0.1-500 and ZnO / ZnO-0.1-600 are better than commercial grade ZnO, indicating that the porous ZnO material derived by calcination of ZIF-8 can provide a larger specific surface area and more active sites, which is beneficial for the pyrolysis of HDU to prepare HDI. However, the catalytic performance of ZnO / ZnO-0.1-600 is lower than that of ZnO / ZnO-0.1-600, which may be due to the high calcination temperature, resulting in severe agglomeration of ZIF-8 at high temperature, and the reduction of specific surface area and activity.
[0051] 4g HDU, 80g dibutyl sebacate, and different amounts of catalyst ZnO / ZnO-0.1-500 (ZnO / ZnO-0.1-500 amounts are 0, 2.5%wt, 5%wt, 7.5%wt, 10%wt, and 12.5%wt of the mass of HDU, respectively) were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced to replace the air in the device, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40min. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. The results are shown in the figure. Figure 3 .
[0052] Depend on Figure 3It can be seen that the use of catalyst has a significant effect on HDU conversion rate, HDI yield and selectivity. When no catalyst is used, the HDU conversion rate is only 53% and the HDI yield is only 23%; with the increase in the amount of catalyst ZnO / ZnO-0.1-500, under the action of the catalyst, the thermal decomposition reaction rate increases, and the selectivity and yield of HDI increase significantly. When the amount of catalyst ZnO / ZnO-0.1-500 reaches 7.5%, the HDU conversion rate reaches 94.3%, and the HDI yield also increases significantly to 81.5%. Subsequently, the amount of catalyst continues to increase, the forward reaction rate is too fast, and the rate of HDI generation is also accelerated, which aggravates the occurrence of side reactions, thereby causing the HDI yield and selectivity to decrease. In this system, the optimal amount of catalyst is 7.5%.
[0053] Example 2
[0054] 3.0 Zn(NO3)2·6H2O was dissolved in 80 mL methanol to form solution A; 4.5 g 2-methylimidazole was dissolved in 60 mL methanol to form solution B; solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 8 h; then 0.24 g Cu(NO3)2·3H2O was added, stirred and dissolved, and aged at room temperature for 2 h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected; the solid was first dried at 65°C for 2 h, and then heated to 100°C and dried for 6 h to obtain a Cu-ZIF-8-0.1 precursor. The Cu-ZIF-8-0.1 precursor was calcined at 450°C in an air atmosphere for 2 h to obtain a multi-component CuO / ZnO-0.1 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 82.3%, specific surface area 36.53m 2 / g, oxygen vacancy concentration O ads / O lat It is 84.17%.
[0055] 3g HDU, 80g dioctyl phthalate (DOP), and 0.375g catalyst were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 230°C and a pressure of 0.09MPa for 30min. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 93.3% and the HDI yield was 85.2%.
[0056] Example 3
[0057] 3.0g Zn(NO3)2·6H2O was dissolved in 50mL methanol to form solution A; 6g 2-methylimidazole was dissolved in 60mL methanol to form solution B. Solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 7h. After adding 0.48g Cu(NO3)2·3H2O, it was stirred and dissolved, and then aged at room temperature for 3h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected; it was first dried at a temperature of 70℃ for 1.5h, and then heated to 90℃ and dried for 8h to obtain a Cu-ZIF-8-0.2 precursor. The Cu-ZIF-8-0.2 precursor was calcined at 500℃ in an air atmosphere for 2h to obtain a multi-component CuO / ZnO-0.2 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 79.5%, specific surface area 39.95m 2 / g, oxygen vacancy concentration O ads / O lat It is 88.42%.
[0058] 4g HDU, 80g dibutyl sebacate (DBS), and 0.3g catalyst were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40min. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 96.5% and the HDI yield was 88.0%.
[0059] Example 4
[0060] 3.0g Zn(NO3)2·6H2O was dissolved in 50mL methanol to form solution A; 5.0g 2-methylimidazole was dissolved in 60mL methanol to form solution B. Solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 8h; 0.29g Co(NO3)2·6H2O was added, stirred and dissolved, and then aged at room temperature for 4h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected; the solid was first dried at 60℃ for 2h, and then heated to 90℃ and dried for 6h to obtain a Co-ZIF-8-0.1 precursor. The Co-ZIF-8-0.1 precursor was calcined at 550℃ in air atmosphere for 1.5h to obtain a multi-component Co3O4 / ZnO-0.1 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 82.1%, specific surface area 34.52m 2 / g, oxygen vacancy concentration O ads / O lat It is 85.63%.
[0061] Add 5g PDU, 80g dioctyl sebacate (DOS), and 0.4g catalyst into a three-necked flask, assemble and build a pyrolysis device with condensation at both ends, set the temperature of the first HDI condensation section to 50°C, and the temperature of the second condensation section to room temperature, introduce nitrogen into the air in the device, and check the air tightness of the device. Carry out catalytic pyrolysis reaction at a temperature of 250°C and a pressure of 0.09MPa for 35min. After the reaction, collect the reaction liquid in the receiving bottle after the two condensations for chromatographic quantitative analysis. After detection and calculation, the PDU conversion rate is 91.5% and the PDI yield is 83.6%.
[0062] Example 5
[0063] 3.0g Zn(NO3)2·6H2O was dissolved in 90mL methanol to form solution A; 6.0g 2-methylimidazole was dissolved in 70mL methanol to form solution B. Solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 7h; 1.5g Al(NO3)3·9H2O was added, stirred and dissolved, and then aged at room temperature for 3h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected; the solid was first dried at 60℃ for 2h, and then heated to 100℃ and dried for 6h to obtain Al-ZIF-8-0.4 precursor. Al-ZIF-8-0.4 precursor was derived by high temperature calcination at 500℃ for 3h in air atmosphere to obtain a multi-component Al2O3 / ZnO-0.4 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 77.2%, specific surface area 20.36m 2 / g, oxygen vacancy concentration O ads / O lat It is 84.25%.
[0064] Add 6g IPDU, 80g dioctyl sebacate (DOS), and 0.5g catalyst to a three-necked flask, assemble and build a pyrolysis device with condensation at both ends, set the temperature of the first HDI condensation section to 50°C, and the temperature of the second condensation section to room temperature, introduce nitrogen into the air in the device, and check the air tightness of the device. Carry out catalytic pyrolysis reaction at a temperature of 240°C and a pressure of 0.09MPa for 50min. After the reaction, collect the reaction liquid in the receiving bottle after the two condensations for chromatographic quantitative analysis. After detection and calculation, the IPDU conversion rate is 92.3% and the IPDI yield is 81.4%.
[0065] Example 6
[0066] 3.0g Zn(NO3)2·6H2O was dissolved in 70mL methanol to form solution A; 5.5g 2-methylimidazole was dissolved in 90mL methanol to form solution B. Solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 8h; 0.8g Cr(NO3)3·9H2O was added, stirred and dissolved, and then aged at room temperature for 6h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected; the solid was first dried at 60℃ for 1h, and then heated to 100℃ and dried for 6h to obtain a Cr-ZIF-8-0.2 precursor. The Cr-ZIF-8-0.2 precursor was calcined at 550℃ for 2h in an air atmosphere to obtain a multi-component Cr3O4 / ZnO-0.2 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 78.6%, specific surface area 36.65m 2 / g, oxygen vacancy concentration O ads / O lat It is 83.84%.
[0067] 6g PDU, 80g dibutyl sebacate (DBS), and 0.5g catalyst were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 230°C and a pressure of 0.09MPa for 30 minutes. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the PDU conversion rate was 90.8% and the PDI yield was 80.4%.
[0068] Example 7
[0069] 3.0g Zn(NO3)2·6H2O was dissolved in 60mL methanol to form solution A; 6.0g 2-methylimidazole was dissolved in 80mL methanol to form solution B. Solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 8h; 0.96g Cu(NO3)2·3H2O was added, stirred and dissolved, and then aged at room temperature for 5h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected. The solid was first dried at 70℃ for 2h, then heated to 90℃ and dried for 6h to obtain a Cu-ZIF-8-0.4 precursor. The Cu-ZIF-8-0.4 precursor was calcined at 500℃ for 1h in an air atmosphere to obtain a multi-component CuO / ZnO-0.4 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 77.8%, specific surface area 18.57m 2 / g, oxygen vacancy concentration O ads / O lat It is 85.45%.
[0070] 4g HDU, 80g dibutyl phthalate (DBP), and 0.3g catalyst were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 250°C and a pressure of 0.09MPa for 45 minutes. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 94.2% and the HDI yield was 84.9%.
[0071] Example 8
[0072] 3.0g Zn(NO3)2·6H2O was dissolved in 100mL methanol to form solution A; 6.0g 2-methylimidazole was dissolved in 60mL methanol to form solution B. Solution A was added to solution B and stirred thoroughly, mixed evenly, and aged at room temperature for 7h; 0.58g Co(NO3)2·6H2O was added, stirred and dissolved, and then aged at room temperature for 2h; the mixed solution was centrifuged to obtain a precipitate, which was washed with fresh methanol and the solid was collected; the solid was first dried at 70℃ for 2h, and then heated to 90℃ and dried for 8h to obtain a Co-ZIF-8-0.2 precursor. The Co-ZIF-8-0.2 precursor was calcined at 500℃ for 3h in an air atmosphere to obtain a multi-component Co3O4 / ZnO-0.2 composite oxide nanocatalyst. Characterization methods such as XRD, BET, XPS, and SEM-Mapping have proven that the catalyst elements are evenly distributed, inherit the nano-morphology and porous structure of the organic metal framework precursor, and have a higher polarity ratio I 002 / 100 (ZnO) = 78.2%, specific surface area 32.83m 2 / g, oxygen vacancy concentration O ads / O lat It is 84.58%.
[0073] Add 2g IPDU, 80g dibutyl sebacate (DBS), and 0.2g catalyst to a three-necked flask, assemble and build a pyrolysis device with condensation at both ends, set the temperature of the first HDI condensation section to 50°C, and the temperature of the second condensation section to room temperature, introduce nitrogen into the air in the device, and check the air tightness of the device. The catalytic pyrolysis reaction was carried out at a reaction temperature of 230°C, a reaction pressure of 0.09MPa, and a reaction time of 50min. After the reaction, the reaction liquid was collected and subjected to chromatographic quantitative analysis. After testing and calculation, the IPDU conversion rate was 95.5% and the IPDI yield was 85.7%.
[0074] Comparative Example 1
[0075] 4 g HDU, 80 g dibutyl sebacate, 0.4 g commercial grade ZnO catalyst (polarity ratio I 002 / 100 (ZnO) = 67.1%, specific surface area 0, oxygen vacancy concentration 77.42%) were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40 minutes. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 89.6% and the HDI yield was 72.6%.
[0076] Comparative Example 2
[0077] 4g HDU, 80g dibutyl sebacate, 0.4g commercial grade CuO catalyst (polarity ratio I 002 / 100 (ZnO) = 0%, specific surface area 0, oxygen vacancy concentration 78.36%) were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40 minutes. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 85.6% and the HDI yield was 59.1%.
[0078] Comparative Example 3
[0079] 4g HDU, 80g dibutyl sebacate, 0.4g commercial grade Cr3O4 catalyst (polarity ratio I 002 / 100 (ZnO) = 0%, specific surface area 0, oxygen vacancy concentration 78.42%) were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40 minutes. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 87.3% and the HDI yield was 36.6%.
[0080] Comparative Example 4
[0081] 4g HDU, 80g dibutyl sebacate, 0.4g commercial grade ZnO and CuO mixture (n Cu :n Zn =0.2:1) as a catalyst (polarity ratio I 002 / 100 (ZnO) = 68.5%, specific surface area 0, oxygen vacancy concentration 78.68%) were added to a three-necked flask, and a pyrolysis device with condensation at both ends was assembled. The temperature of the first HDI condensation section was set to 50°C, and the temperature of the second condensation section was set to room temperature. Nitrogen was introduced into the air in the device to replace the air, and the air tightness of the device was checked. The catalytic pyrolysis reaction was carried out at a temperature of 240°C and a pressure of 0.09MPa for 40 minutes. After the reaction, the reaction liquid in the receiving bottle after the two condensations was collected and chromatographic quantitative analysis was performed. After detection and calculation, the HDU conversion rate was 90.3% and the HDI yield was 76.7%.
Claims
1. An oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis, characterized in that: It uses Zn(NO3)2·6H2O and 2-methylimidazole as raw materials to prepare ZIF-8 imidazole zeolite framework; then, metal nitrate M(NO3) is used for impregnation. x · y H2O makes the metal ions M x+ Replacement of part of Zn in the imidazolate framework of ZIF-8 2+ , and obtain the M-ZIF-8 precursor; the M-ZIF-8 precursor is calcined at 400-600°C for 1-10 h in an air atmosphere to obtain MO z / ZnO oxide-based nanocatalyst; The molar ratio of the metal nitrate to Zn(NO3)2·6H2O is 0.1:1 to 0.4:1; The metal nitrate M(NO3) x ·yH2O is selected from one of Zn(NO3)2·6H2O, Cu(NO3)2·3H2O, Co(NO3)2·6H2O, Al(NO3)3·9H2O, and Cr(NO3)3·9H2O.
2. The oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis according to claim 1, characterized in that: The molar ratio of the 2-methylimidazole to Zn(NO3)2·6H2O is 5:1 to 7.5:
1.
3. The oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis according to claim 1, characterized in that: The molar ratio of the metal nitrate to Zn(NO3)2·6H2O is 0.1:1 to 0.2:
1.
4. A method for preparing an oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis according to claim 1, characterized in that: include: Dissolve Zn(NO3)2·6H2O in a reaction solvent to form a zinc nitrate solution; dissolve 2-methylimidazole in a reaction solvent to form a 2-methylimidazole solution; mix the zinc nitrate solution and the 2-methylimidazole solution evenly, and age at room temperature for 6 to 12 hours to obtain a suspension containing a ZIF-8 imidazole zeolite framework; then add a metal nitrate M(NO3) x · y H2O, stirred to dissolve, aged at room temperature for 1 to 6 h, the mixed solution was centrifuged to obtain a precipitate, the precipitate was washed with methanol, the solid was collected, and the solid was dried to obtain an M-ZIF-8 precursor; the M-ZIF-8 precursor was calcined at a high temperature of 400 to 600 ° C in an air atmosphere for 1 to 10 h to obtain MO z / ZnO oxide type nanocatalyst.
5. The method for preparing an oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis according to claim 4, characterized in that: The zinc nitrate solution is prepared by mixing a reaction solvent with Zn(NO3)2·6H2O in a mass ratio of 16:1 to 27:1; the 2-methylimidazole solution is prepared by mixing a reaction solvent with 2-methylimidazole in a mass ratio of 8:1 to 14:1; the reaction solvent is methanol, deionized water or N,N-dimethylformamide.
6. The method for preparing an oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis according to claim 4, characterized in that: The solid is first dried at a temperature of 60-70°C for 1-2 hours, and then heated to 80-100°C and dried for 6-10 hours, or the solid is dried at 80-100°C for 6-10 hours.
7. The method for preparing an oxide-type catalyst for preparing aliphatic isocyanate by catalytic pyrolysis according to claim 4, characterized in that: The calcination temperature is 450-550°C.
8. A method for preparing aliphatic isocyanate by catalytic pyrolysis of aliphatic carbamate, characterized in that: include: The oxide-type nanocatalyst according to claim 1 is used as a catalyst, and a high-boiling-point solvent is used as a reaction solvent to catalyze and pyrolyze aliphatic carbamate to prepare aliphatic isocyanate; wherein the reaction temperature is 220-260°C, the reaction pressure is 0.01-0.1 MPa, and the reaction time is 20-60 min; the mass ratio of the catalyst to the aliphatic carbamate is 0.025-0.125:1; the aliphatic carbamate is selected from one of pentamethylene dicarbamate, hexamethylene dicarbamate, and isophorone dicarbamate; and the high-boiling-point solvent is an organic solvent with a boiling point of 330-450°C.
9. The method for preparing aliphatic isocyanate by catalytic pyrolysis of aliphatic carbamate according to claim 8, characterized in that: The reaction temperature is 230-250°C, the reaction pressure is 0.01-0.09MPa, and the reaction time is 30-50min; The high boiling point solvent is selected from one of dibutyl phthalate, dioctyl phthalate, dibutyl sebacate and dioctyl sebacate; The mass ratio of the aliphatic carbamate to the high boiling point solvent is 0.025:1 to 0.075:1; The mass ratio of the catalyst to the aliphatic carbamate is 0.05:1 to 0.1:
1.
10. The method for preparing aliphatic isocyanate by catalytic pyrolysis of aliphatic carbamate according to claim 9, characterized in that: The high boiling point solvent is selected from one of dibutyl sebacate and dioctyl sebacate.
11. The method for preparing aliphatic isocyanate by catalytic pyrolysis of aliphatic carbamate according to claim 9, characterized in that: The mass ratio of the aliphatic carbamate to the high boiling point solvent is 0.0375:1 to 0.05:1.
Citation Information
Patent Citations
Method for producing 1,6-hexamethylene diisocyanate with hexa-methylene diamino-methyl formate liquid phase thermal cracking
CN101195590A
Method for preparing hexamethylene-1,6-diisocyanate (HDI) by heterocatalytic pyrolysis in liquid phase
CN102964272A